Prey availability and juvenile Atlantic salmon feeding during winter in a regulated subarctic river subject to loss of ice cover - Johansen, M; Thorstad, E. B; Rikardsen, A. H; Koksvik, J. I; Ugedal, O; Jensen, A. J; Saksgård, L; Næsje, T. F (Hydrobiologia, 2010)
Increased mortality of juvenile Atlantic salmon (Salmo salar L.), related to lowered levels of stored energy following the loss of ice cover during winter, has been observed after hydropower development in the subarctic River Alta, northern Norway. Drift samples were compared to examine if drift densities, and thus drift prey availabilities for juvenile salmon, were lower in the ice-free than the ice-covered area. In addition, juvenile salmon stomach contents were compared to benthos and drift in the ice-free area to examine salmon winter feeding habitat. Zooplankton, originating from the reservoir, dominated drift at the ice-free site but had lower densities at the downstream ice-covered site. Excluding zooplankton, Chironomidae comprised most of the remaining drift at both the ice-free and ice-covered site, followed by Ephemeroptera, Plecoptera and Simuliidae. No Trichoptera were found in the drift samples. There was no consistent diel periodicity in drift. Benthos was dominated by Chironomidae, followed by Ephemeroptera, Plecoptera and Trichoptera. Other invertebrates occurred in low numbers. Juvenile salmon demonstrated size-selective feeding and fed mainly on Ephemeroptera, followed by Trichoptera and Plecoptera. No zooplankton and few Chironomidae were found in the stomach samples. Stomach content was more similar to benthos than to drift, indicating a larger extent of benthic than drift feeding. No evidence was found for the hypothesis that lack of ice cover reduced the invertebrate drift or caused diel periodicity in the drift. Differences in drift between areas with and without ice could not account for the observed differences in mortality of juvenile salmon during the winter in these areas.